2006
DOI: 10.1097/01.gim.0000195894.67756.8b
|View full text |Cite
|
Sign up to set email alerts
|

What is in a cause? Exploring the relationship between genetic cause and felt stigma

Abstract: Purpose: Concern over stigma as a consequence of genetic testing has grown in response to the recent increase in genetic research and testing resulting from the Human Genome Project. However, whether a genetic or hereditary basis necessarily confers a stigma to a condition remains unexamined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 37 publications
1
52
0
1
Order By: Relevance
“…Approval for the exempt status of the study was obtained from the Vanderbilt University Institutional Review Board. The NSS-C data provides an opportunity to examine variance in and factors associated with attributions and stigma when the public is confronted with a child's mental illness (depression and attention deficit hyperactivity disorder, ADHD) versus a child's physical illness (asthma) similar to some adult mental health studies (e.g., Sankar et al 2006). In the original NSS-C study, a nationally representative sample of US adults (N = 1,372) were each presented with vignettes that included a hypothetical description of a child with a health condition.…”
Section: Methodsmentioning
confidence: 99%
“…Approval for the exempt status of the study was obtained from the Vanderbilt University Institutional Review Board. The NSS-C data provides an opportunity to examine variance in and factors associated with attributions and stigma when the public is confronted with a child's mental illness (depression and attention deficit hyperactivity disorder, ADHD) versus a child's physical illness (asthma) similar to some adult mental health studies (e.g., Sankar et al 2006). In the original NSS-C study, a nationally representative sample of US adults (N = 1,372) were each presented with vignettes that included a hypothetical description of a child with a health condition.…”
Section: Methodsmentioning
confidence: 99%
“…Ten qualitative studies were identified and explored family discord [13], experience, physical, and psycho-social well being of women with breast cancer under the age of 40 who are BRCA1/2 mutation carriers [14], stigma associated with genetic disease [15], moral and social effects of having genetic testing [16], long term coping strategies and unmet needs of women at increased risk for breast cancer [17], experiences of women having prophylactic mastectomy [18,19], responses to BRCA1/2 testing [20][21][22] and how women live with increased risk [23] (See Table 1). Twenty seven quantitative studies were identified (See Table 2).…”
Section: Designmentioning
confidence: 99%
“…Mastery and self-esteem have not been studied in terms of whether they are related to positive adjustment with genetic test result receipt, nor have feelings of stigmatization (except for qualitative analyses) [19]. Due to inconsistent findings on long-term adjustment of carriers [2][3][4], we wanted to explore whether mood disturbances vary as a function of time following test result receipt in a large cohort of BRCA1/2 carriers with considerable variability in time since carrier notification.…”
Section: Introductionmentioning
confidence: 99%